CREATION OF AN IMMOBILIZED PROBIOTIC BASED ON BACTERIAL CELLULOSE FOR THE CORRECTION OF THE INTESTINAL MICROBIOME (Experimental biology, 2023)
The structural features of bacterial cellulose (BC) make it very popular to use it for creating composite materials. Immobilization of bacteria of the Bacillus genus in BC polymer gives the carrier matrix new functional properties that help restore and maintain a favorable balance of microflora in the gastrointestinal tract. The addition of sodium alginate had a positive effect on the synthesis of BC by K. xylinus C-3, providing a polymer yield of 12.11 g/l.  The "adsorption-incubation" method was used for surface and spatial immobilization of Bacillus subtilis, which provides a high concentration of cells – 108 CFU per 1 g of carrier. The BC/Bacillus biocomposite inhibited the growth of E. coli, S. typhi, S. typhimurium, Citr. aerogenes, and P. vulgaris up to 85.4% after 24 hours of contact, and after 72 hours completely inhibited the growth and viability of test organisms in vitro. Immobilized probiotics significantly exceeded the suspension of free microbial ells in terms of resistance to gastric juice. The activity of probiotics in vivo determined on models of experimental dysbiosis. Probiotic microgranules of BC/B.subtilis can be used to correct the microbiocenosis of the large intestine.
Keywords: bacterial cellulose, B. subtilis, dysbiosis